2005
DOI: 10.31421/ijhs/11/4/601
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of the sour cherry verticum in the Northern Great Plain Region Hungary (Analytic study)

Abstract: Sour cherry growing and consumption grows dynamically around the world. The present volume of 1 million tons will incerase within 10 years with 20-30, or even with 50%. In the world wide sour cherry production, Europe is a decisive factor, i.e. 2/3 of the volume is grown there. Prominent capacities are concentrated in East-Central Europe, mainly Poland, Germany and Hungary. In the future, new concurrent exporters are expected on the European market as Turkey, Iran, Serbia-Montenegro. Hungarian sour cherry prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For this reason, the latter is not recommended as a pollinating cultivar for the others grown in Ain-Draham. According to Nyeki [34], for the sweet cherry tree, a…”
Section: Comparison Of Blooming Period In the Three Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the latter is not recommended as a pollinating cultivar for the others grown in Ain-Draham. According to Nyeki [34], for the sweet cherry tree, a…”
Section: Comparison Of Blooming Period In the Three Sitesmentioning
confidence: 99%
“…The duration of the stigma's viability is influenced by weather factors. Regarding sour cherries, Nyeki [34] observed that the viability of the stigma was 2-3 days during sunny and hot days (mean daily temperature is 15-22°C). The viability was longer (4-6 days) in cool weather and daily temperatures of 4-12°C.…”
Section: Effect Of Temperature (Maximum) During Blooming Period On Frmentioning
confidence: 99%
“…Sour cherries are consumed fresh in Hungary and in some Northern-European countries, as the domestic cultivars do not contain bitter substances. Cultivar use is determined by the way of consumption (Nyéki et al, 2005;Szabó, 2007). Sour cherry producing countries grow only one or two cultivars in largest proportion.…”
Section: Introductionmentioning
confidence: 99%